The Dynamics of Press Freedom in the Midst of the Implementation of the ITE Law and the Criminal Code: A Study of Legal Sociology - Ihsan Mahfudz; Ahmad Jamaludin (Jurnal Mahkamah : Kajian Ilmu Hukum dan Hukum Islam, 2026)
Press freedom is currently facing new challenges along with the development of information technology. In the midst of the application of the ITE Law and the Criminal Code on press freedom, it has caused a special debate about the boundary between enforcement and protection of press activities. Although press freedom has been specifically regulated in Law No. 40 of 1999 concerning the Press, law enforcement practices still show the use of other articles that have the potential to limit press activities. This study aims to analyze juridically and sociologically the dynamics of press freedom in the implementation of the ITE Law and the Criminal Code in Indonesia. The method used is normative legal research with a legal, conceptual, and sociological approach to law, through the study of legal norms, principles, and doctrines relevant to press freedom. The results of the study show that the ITE Law and the Criminal Code on press freedom often override the press law as lex specialis. As a result, the settlement of press disputes is easily contravened by interests directed at the criminal mechanism rather than the ethical mechanism and the right of reply that has been regulated in the press law. This condition has a juridical effect, legal and sociological uncertainty, resulting in a chilling effect for press personnel and potentially limiting the function of the press as a supervisor of power. This research contributes to the development of press law through strengthening the concept  of lex specialis of the Press Law and harmonizing regulations to ensure the protection of press freedom in a democratic legal country.